Effectiveness of AR-Guided Inquiry E-Worksheets on Students’ 21st-Century Skills in Science Lessons, Examined by Gender and Learning Style - M. Ibnusaputra; Putri Surya Damayanti; Febriani Febriani (Journal of Insan Mulia Education, 2026)
This study aims to analyze the effectiveness of using guided inquiry-based e-worksheets incorporating Augmented Reality (AR) on the development of students’ 21st-century skills in science learning, as viewed through the lens of gender and learning style differences. The study employs a quantitative approach with a pretest–posttest control group quasi-experimental design. The research subjects were eighth-grade students at a public junior high school in Bima City, divided into an experimental group (using AR-based e-worksheets) and a control group (using conventional worksheets). Data were collected through critical thinking skill tests, observation sheets for collaboration, communication, and creativity, as well as a learning style questionnaire. Data analysis was conducted using ANOVA, GLM, Bonferroni post hoc tests, and n-gain scores. The results indicated that the implementation of AR-integrated guided inquiry e-worksheets significantly influenced the improvement of 21st-century skills (sig. = 0.008 < 0.05), with an average n-gain score of 65.38% (classified as moderately effective). Gender and learning style did not significantly influence learning outcomes, indicating that the learning process was inclusive and adaptive. The highest improvement occurred in creativity skills, followed by communication, collaboration, and critical thinking. These findings confirm that the integration of AR into inquiry-based learning creates a contextual, interactive, and reflective learning environment that supports the comprehensive development of 21st-century skills.